Implementation of Strategic Management in the Framework of Improving the Performance of Maritime Public Service Agencies Case Study of Blu PIP Makassar - Amran, Amran; Syuthi, Nurmadhni Fitri; Syamsidar, St; Azis, Agung Firmansyah (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
Maritime education industry in Indonesia has a significant role to contribute to the development of the nation, as Indonesia has expansive archipelagic territory and increased maritime duties on an international scale. This paper seeks to measure how strategic management can help in improving institutional performance at the BLU PIP Makassar in the use of aggressive approach within the institution using a hybrid of the SWOT analysis, Quantitative Strategic Planning Matrix (QSPM) and the Balanced Scorecard (BSC). Quantitative research design was utilised to develop data on 50 purposively sampled respondents in the planning and the HR units. The analysis of the instrument validity and reliability was verified by Pearson correlation and Cronbach Alpha testing. Linear regression analysis was used to study the relationship amid strategic management implementation and institutional performance. The results prove the positive correlation (R = 0.825) and the significant regression coefficient (beta = 0.712, p < 0.001) which means that the impact of strategic management on the performance outcomes proves its importance. Learning and growth and customer satisfaction were noted to improve significantly by +23 and +14 percent respectively. This work does not only provide empirical support regarding the success of integrated strategic instruments in the environment of the public service but also contributes to filling one of the gaps in the localized research on the maritime education management in Indonesia.